If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
x = 0
x^2 = 0
x = 0
x = 0
x^2 = 0
x^2 = 0
1*x^2 = 0 // : 1
x^2 = 0
x = 0
x in (-oo:0) U (0:+oo)
4-(1/x) = 3/(x^2) // - 3/(x^2)
4-(1/x)-(3/(x^2)) = 0
4-x^-1-3*x^-2 = 0
t_1 = x^-1
4-3*t_1^2-1*t_1^1 = 0
4-3*t_1^2-t_1 = 0
DELTA = (-1)^2-(-3*4*4)
DELTA = 49
DELTA > 0
t_1 = (49^(1/2)+1)/(-3*2) or t_1 = (1-49^(1/2))/(-3*2)
t_1 = -4/3 or t_1 = 1
t_1 = -4/3
x^-1+4/3 = 0
1*x^-1 = -4/3 // : 1
x^-1 = -4/3
-1 < 0
1/(x^1) = -4/3 // * x^1
1 = -4/3*x^1 // : -4/3
-3/4 = x^1
x = -3/4
t_1 = 1
x^-1-1 = 0
1*x^-1 = 1 // : 1
x^-1 = 1
-1 < 0
1/(x^1) = 1 // * x^1
1 = 1*x^1 // : 1
1 = x^1
x = 1
x in { -3/4, 1 }
| 6(2n-3)=13n+18 | | 3.78= | | 2h+7=3h | | 4a+24=84 | | 5s=5s+4 | | 35x+2=9x+2 | | 45x+71=-12+45x | | 2x^3+4x^2+3x+1=0 | | 3x-5/2=x | | 4X-7=8X | | 5-7m=3m | | 5(x-10)=2(x+8) | | 14-3(2x-1-2(3x+1))=6x-1 | | 4x-20=3x+11 | | 4x^3-28x^2+48x-8=0 | | -2(-3b+4.8)=14.4 | | 6x^2-7xr+2r^2=0 | | y=8-2x-x^2 | | 5(x-10)=(x+8) | | 5b+4=3b-4 | | -26x+60=79+84x | | 3+5x=11+3x | | 5(x+10)2x=246 | | 3x*2xy+xy= | | A=6(2x-3)+2(3-2x) | | x^2=100+10x | | 6×1/2-7 | | 2x+35=5x-85 | | 10k=4k-16 | | y=2+3x+6x^2 | | 1/2x=34=48 | | 10x+2(141x)=-2 |